Intelligent 'Salai' Oven with adaptive controller - Mohd. Sabri, Hussin; Sarif Hashim, Sarif Hassan; Nor Zaiazmin, Yahaya; Mohd Sazli, Saad; Azuwir, Mohd Nor; Mohd Zaki, Abd. Muin, Prof (Universiti Teknologi MARA, Kedah, 2010)
Invention, Innovation & Design (IID Kedah 2010), 28th - 29th July 2010 organized by Universiti Teknologi MARA (UiTM), Kedah at SP Inn, Kedah.